The Impact of Leadership Style on Employee Job Satisfaction in Sports Sector in Qatar - Hashimi, Adel Mohammed Ibraheem (The Arab Journal of Administration, 2024)
The current study aims to identify the most used leadership styles in the sports sector in the State of Qatar, in addition to studying the impact of leadership styles (dictatorial, democratic, laissez-faire) on the job satisfaction of employees in the sports sector in the State of Qatar. The descriptive analytical approach was used by distributing a questionnaire to a simple random sample of employees in the official sports sector, where the number of questionnaires retrieved and suitable for analysis reached 53 questionnaires. They were analyzed using appropriate descriptive and analytical methods in SPSS. The results showed that the most widely used leadership style in the sports sector in the State of Qatar is the democratic style. It also showed that the level of job satisfaction among employees in the sports sector was high. It was found that there was a negative correlation between both the dictatorial style and the laissez-faire style and job satisfaction, and positive correlation between the democratic style and job satisfaction. It was also shown that there is a negative impact of leadership styles (dictatorial and laissez-faire) on employee satisfaction.